Physicochemical, Antioxidant and Sensory Characteristics of Cookies Incorporating Pineapple Core Powder - Wan Ab Halim, Wan Hadibah; Basri, Hatijah (Enhanced Knowledge in Sciences and Technology, 2025)
Cookies are one of the most consumed bakery products worldwide, and efforts to enhance their nutritional profile while minimizing food waste are increasingly gaining attention. This study investigates the incorporation of pineapple core powder (PCP), an underutilized by-product rich in antioxidants, as a functional ingredient in cookie formulations. The research aims to evaluate the effects of PCP substitution at 0% (control), 20%, 50%, and 100% on antioxidant activity, physicochemical properties (moisture content, texture, colour), and sensory acceptability. The antioxidant activity, determined by the DPPH radical scavenging assay, increased significantly (p < 0.05) with higher PCP levels, reaching 88.39% and 90.59% for the 50% and 100% formulations, respectively, compared to 34.22% in the control. Physicochemical analysis showed that increasing PCP content led to darker coloration (lower L values), increased hardness, and higher moisture content*, which could impact shelf-life and textural characteristics. The texture profile analysis (TPA) revealed that cookies with 100% PCP were the hardest (6.922 ± 0.496 kg force), while the control exhibited the softest texture (3.854 ± 0.146 kg force), suggesting a strong correlation between fiber content and firmness. Sensory evaluation by 50 untrained panellists using a 9-point hedonic scale indicated that the 50% PCP formulation (AC50) was the most preferred, achieving the highest overall acceptability score of 6.94 ± 1.659, while the 100% PCP formulation (AC100) was rated lower due to excessive firmness and intensified bitterness. These findings highlight the potential of pineapple core powder as a sustainable, antioxidant-rich ingredient in bakery applications, offering a viable alternative for functional food development. Further research should explore the impact of PCP on shelf stability, bioactive compound retention during storage, and its interaction with other ingredients to optimize product quality and consumer acceptability.